Long-term rainfall and water table influence on groundwater nutrient dynamics from an oil palm plantation - Felicia Unda Anggat; Soh-Fong Lim; Yau-Seng Mah; Nur Azima Busman; Nagamitsu Maie; Faustina Sangok; Lulie Melling (Water Science)
Conservation of groundwater quality is of paramount importance for sustainable agricultural management. Hydrological factors such as rainfall patterns and water table (WT) management, including drainage practices, play a crucial role in groundwater recharge. This in turn has a significant impact on WT fluctuations, nutrient losses in the soil, and the leaching of fertilizers into groundwater which leads to groundwater pollution. Consequently, this study evaluates the long-term influence of seasonal rainfall and WT fluctuations on groundwater nutrient dynamics in tropical peatlands from an oil palm plantation (OPP). Linear regression analyses and Pearson correlation matrices were adopted to evaluate the relationships between seasonal rainfall, WT, and groundwater chemical parameters. The results showed that there was a significant increase in mean pH, NO3−, Na+, Ca2+, and PO43- values during the wet season compared to the dry season which could be attributed to the leaching of nutrients into groundwater due to rainfall, nutrient runoff from drainage systems and increased nitrification rate. A significant positive correlation (p < 0.01) was found between groundwater pH and NO3− during the wet season, suggesting that increased groundwater pH due to heavy rainfall directly affects the nitrification process. It was also observed that low WT promotes denitrification in shallow groundwater, with this effect being more significant (p < 0.05) during the dry season. This was reflected in the higher correlation values between the WT fluctuations and the NH4+ concentrations in the groundwater. This research represents the first study to explore the long-term impacts of rainfall and WT fluctuations on groundwater quality in tropical peatlands. The insights gained from this study offer valuable guidance for WT management strategies aimed at conserving groundwater quality in such environments, ultimately contributing to sustainable agricultural practices.